Quantification and spatial assessment of industrial Cd and Pb emission across India - Madhusmita Mishra; Ashirbad Mishra; Poonam Mangaraj; Atul Kumar Srivastava; Gufran Beig; Pallavi Sahoo; Sridhara Nayak; B. Anjan Kumar Prusty; Arti Choudhary; Saroj Kumar Sahu (All Earth, 2025)
Heavy metals, particularly cadmium (Cd) and lead (Pb), pose a significant environmental challenge worldwide owing to their detrimental effects on ecosystem sustainability. India, the most populous country in the world, presently faces severe contamination by heavy metals. This study identifies and quantifies the Cd and Pb emissions from the principal industrial sources at the district level across India, using the IPCC bottom-up approach for 2019. The developed emission inventory includes various industries, notably coal-based power plants, captive power plants, cement production, iron and steel manufacturing, non-ferrous metal production, municipal and biomedical waste incineration, the glass industry, and fly ash generated. Annual emissions were reported to be approximately 2,016 tonnes/year (t/yr) for Cd and 19,258 t/yr for Pb, where coal combustion across different industries emitted approximately 93 t of Cd and 927 t of Pb, with the energy sector contributing about 66% and fly ash accounting for over 80% of total emissions. Among non-ferrous metals, copper production is solely responsible for 44 t and 77 t of Cd and Pb, respectively. The research also identifies regional hotspots for Cd and Pb emissions across India, highlighting areas where targeted remediation strategies can support sustainable environmental management.